Allogeneic hematopoietic stem cell transplantation in infants is associated with significant morbidity and mortality. (5th February 2022) - Oikonomopoulou, Christina; Paisiou, Anna; Ioannidou, Eleni‐Dikaia; Komitopoulou, Anna; Kaisari, Aikaterini; Zisaki, Kalliopi; Kastamoulas, Michalis; Stavroulaki, Georgia; Giannakopoulou, Aikaterini; Vessalas, George; Kitra‐Roussou, Vassiliki; Goussetis, Evgenios; et al.
Abstract: Background: Infants are subjected to hematopoietic stem cell transplantation (HSCT) due to malignant and non‐malignant diseases. However, specific data concerning the outcome and transplantation‐related complications in infants, as a separate age group, are limited. Our aim was to evaluate the impact of infancy on the outcome, toxicity, and complications after HSCT. Methods: We retrospectively analyzed data of 55 infants that underwent HSCT in our unit from May 1997 until February 2020, emphasizing on the probability of overall survival (OS) and the cumulative incidence (CI) of transplantation‐related mortality (TRM) and complications. Results: We report a probability of OS of 61%, a CI of TRM at day 100 and 365 post transplantation of 22% and 30%, respectively, and additionally a CI of graft failure, acute graft‐versus‐host disease (GvHD), and infectious complications, 18%, 44%, and 39%, respectively. No statistically significant association was detected between the above mentioned parameters and diagnosis, the use of myeloablative or non‐myeloablative/reduced toxicity conditioning regimens or the type of donor. Conclusions: We conclude that HSCT in infancy is associated with significant mortality and morbidity. This is possibly attributed to endogenous, age‐related factors. More specifically, infants may be at a higher risk of toxicities due to the immaturity of developing vital organs and the deficiency of the newly adopted immune system that predisposes them to infectious complications. The development of GvHD further augments the danger of infections, in a potential vice‐versa relationship. Moreover, there are few data on pharmacokinetics of chemotherapy agents, making safe and efficacious drug administration hard.